CISRP: connectivity‐aware intersection‐based shortest path routing protocol for VANETs in urban environments. Issue 3 (1st May 2018) - Nooji Venkatramana, Dharani Kumari; Banagiri Srikantaiah, Shylaja; Moodabidri, Jayalakshmi
Abstract : Vehicular ad hoc networks (VANETs) are a key technology for intelligent transportation system providing different services in safety and entertainment applications. Routing in VANET encounters high mobility of nodes, heterogeneous node distribution and dynamic network topology. These characteristics of the VANET demand a routing protocol capable of inhibiting intermittent connectivity due to network fragmentation. The proposed work is a connectivity‐aware intersection‐based shortest path routing protocol (CISRP) for VANETs in an urban environment. The CISRP has been designed to look into the prevailing road conditions and route the packets in a less congestion and less link breakage path to avoid intermittent connectivity. The results evaluated show the enhanced performance of the CISRP protocol.